Complex method of the knowledge management efficiency evaluation in the project environment - Vartanyan, Vasily; Shteinbrekher, Daria (Національний технічний університет "Харківський політехнічний інститут", 2019)
There are a large number of modern approaches to the development and implementation of organizational knowledge management systems, methodologies and models of knowledge management. Each of them has its own peculiarities, advantages, and disadvantages, aimed at supporting the knowledge saving process. At the same time, the question of the knowledge system effectiveness remains unclear, what complicates the decision-making process. The article analyzes modern approaches to assessing the effectiveness of the knowledge management system and the feasibility of its implementation in the project environment. The approaches analyzed, such as Kaplan-Norton's Balanced Scorecard (Kaplan-Norton), Non-material Asset Monitor (K.Sweeb), Skandia Navigator (Edvinsson), etc., can be used as macro indicators to determine the benefits of Knowledge Management System, but these indicators cannot reflect actual benefits gained solely by this system in relation to business processes and organizational project objectives. Thus, the actual scientific taskis not only to develop a specific method of quantifying the benefits that the Knowledge Management System provides, but also to create indicators for project implementation evaluation through Knowledge Management System efficiency. The paper objectiveis to develop a comprehensive method for evaluation of the effectiveness of the Knowledge Management System, taking into account the specifics of project management. The proposed model is a multi-stage process, which allows increasing the reliability of the final decisions on knowledge management in the project and evaluating the profitability of the system. In addition, the model allows reducing the cost of the project, by simulating the influence of the system elements on project parameters. The proposed model is aimed at optimization (the choice of the best algorithm from several), identification (the definition of a system with the most relevant qualifications to the real object in the given conditions) or decision-making on Knowledge Management System in a project environment. Further researchwill be aimed at the development of automated tools for implementing the model, which will optimizethe use of the model in project-oriented organizations.

Відсутність методів кількісної оцінки переваг, отриманих організацією від впровадження управління знаннями (УЗ) в проектному середовищі ускладнює процес прийняття рішень щодо об’ємів інвестування та їх подальшого використання під час реалізації проектів, тому актуальною науковою задачею є розробка методів та індикаторів, які дозволяють підвищити вимірюваність переваг УЗ. Мета статті полягає в розробці комплексного методу оцінки ефективності системи УЗ, який враховує специфіку проектного менеджменту і дозволяє розробити систему індикаторів для прийняття рішень щодо її рентабельності. В статті проведено аналіз сучасних підходів до оцінки ефективності системи управління знаннями, таких як метод збалансованих показників Каплана-Нортона, Монітор нематеріальних активів К. Свейбі, Навігатор «Skandia» Л. Едвінссона та ін. Визначено недоліки їх використання для аналізу системи УЗ в проектному середовищі. Розглянуто ключові етапи побудови методу оцінки ефективності системи управління знаннями в проектному середовищі. Запропонований багатоетапний процес дозволяє не тільки підвищити достовірність остаточних рішень щодо управління знаннями в проекті та оцінити рентабельність системи, але й знизити витрати проекту за рахунок моделювання впливу елементів системи на його показники. Використання запропонованого методу дозволяє отримати економію до 31.4% бюджету проекту та 40.2% тривалості проекту. Запропонований метод може використовуватись для підтримки прийняття рішень щодо ефективності системи УЗ високотехнологічних проектів.
Комплексний метод оцінки ефективності системи управління знаннями в проектному середовищі
Keywords: model; intellectual capital; модель; інтелектуальний капітал